Construction of a gene knockout cassette for leucosporidium antarcticum - Koh, Joseph Soon Peng (2011)
Leucosporidium .antarcticum, a psychrophilic yeast was isolated from Antarctica. It grew optimally at 12Â°C, and adapted well to the cold temperature in Antarctic. The whole genome of the L. antarcticum has been sequenced using the 454 system. It is ideal to conduct systematic knockout of genes to determine its gene function especially .genes that are responsible for the adaption to the cold. Hence, there is a need to construct a knock-out system for L. antarcticum. The gene knockout constructs were built .by fusing ,an .antibiotic (Genetidn-E418) resistance .gene, KanMX used for gene knock out in Saccharomyces cerevisiae to a series of L. antarcticum gene's promoters. The gene promoters used belonged to the ACT, SNF and Cydophilic genes of L. antarcticum. Gene fusion was conducted using the. polymerase chain reaction (PCR). One set of primer was designed to amplify the genes' promoter region with an overhang that was homologous to the second set of primer used to amplify the KanMX.gene. The promoter that was fused to the KanMX gene was cloned onto a CloneJet Vector (Fermentas) and subsequently used as the template to prepare the gene knock-out DNA fragment for L. antarcticum. The significances of the study involved the verification of the putative promoters obtained from L. antarcticum in the expression of the kanMX gene, secondly, the constructed gene knockout cassette can be used to knockout the targeted gene in order to reveal the function of the gene, and lastly, to demonstrate that gene fusion can be established seamlessly using PCR. Preliminary transformation of L. antarcticum using knockout cassette constructed was tested by using electroporation and' heat-shock transformation systems applied in S. cerevisiae. The transformation of L. antarcticum was not successful. L. antarcticum's colonies were found after electroporation transformation but did not grow onto .the medium containing geneticin (G418). No colony was found after heat-shock transformation.